Combination of new biologic parameters as a prognostic index in epithelial ovarian carcinoma - Kaufmann, Manfred; Minckwitz, Gunter von; Kühn, W.; Schmid, Hans; Costa, Serban-Dan; Goerttler, Klaus; Bastert, Gunther (International journal of gynecological cancer, 1995)
In a total of 77 patients with epithelial ovarian carcinomas, new biologic parameters [estrogen and progesterone receptor (ER, PR), DNA-ploidy (DP), S-phase fraction (Spf), cycling index (Ki67), Her2b/neu oncoprotein, epidermal growth factor receptor (EGF-R), cathepsin D and P170 glycoprotein] have been simultaneously detected and correlated to the clinical outcome [progression-free (PFI) and overall survival (OAS)] in a preliminary study. Apart from conventional prognosticators (age, stage, grade, residual tumor) and the postoperative serum marker Ca125, DP (P = 0.01), Spf (P = 0.009), Ki67 (P = 0.05) and PR (P = 0.01) could predict a short OAS (log rank test), whereas cathepsin D was of borderline significance only. Prognostic significance could be improved by using combinations of different factors [two markers of differentiation (DP, PR), one marker of proliferation (Spf) and one marker describing local tumor spread (cathepsin D)]. The difference in prognosis between patients with either all or three favorable tumor factors and patients with two to four unfavorable tumor factors reached a similar significance as can be obtained using FIGO stage as a prognostic factor (P = 0.007 for PFI, P = 0.0005 for OAS). These results were similar if early stages (FIGO I and II) were excluded. However, in a Cox regression analysis, including stage and residual tumor, this combination was significantly independent for PFI and OAS and could give additional information. Therefore, the large number of new biologic tumor markers could be restricted to only a few significant prognosticators to predict prognosis in primary epithelial ovarian carcinoma. In the future tumor characterizations may allow more individualized treatment with more aggressive, or even without, cytotoxic therapy after primary surgery.